(untitled) (Journal Of Educational and Psychological Researches, 2022)
The research seeks to identify the effectiveness of a selective program in modifying irrational thinking that causes anger among an important class of societies in general. namely teachers. Specifically female teachers because of the pressures they suffer because of the nature of this profession. It may develop into anger outburst, which may cause irrational thinking arose as a result of the different situations they are going through. The sample of the program consisted of (12) teachers in Egypt, from different educational sectors. The researcher intended to clarify the emotion of anger and the irrational thoughts associated with it and the contribution of the selective counseling program in modifying those irrational thinking. This was rooted during the presentation of the theoretical framework and previous studies, the study terminology, objectives and importance of the study. The study was determined by a set of tools prepared by the researcher: the irrational thoughts scale of anger, the selective counseling program. The results of the research indicated the effectiveness of the selective extension program. The research concluded with a set of recommendations and suggestions.